2021
DOI: 10.1080/20008198.2021.1994218
|View full text |Cite
|
Sign up to set email alerts
|

Mental health in adult refugees from Syria resettled in Norway between 2015 and 2017: a nationwide, questionnaire-based, cross-sectional prevalence study

Abstract: Background The number of forcibly displaced people globally has never been higher, with refugees from Syria constituting the largest displaced population worldwide. Many studies have documented elevated levels of mental health problems in refugee populations, though prevalence estimates of common mental disorders vary considerably between studies, explained both by methodological and contextual factors. Objective Using questionnaire-based screening checklists to approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Another study [ 30 ] found differences in reporting anxiety and PTSD symptoms between asylum seekers and individuals with residence permit, but not in depressive symptoms. Five studies found no significant association between legal status and symptoms of depression, anxiety, or PTSD [ 21 , 26 , 29 , 31 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study [ 30 ] found differences in reporting anxiety and PTSD symptoms between asylum seekers and individuals with residence permit, but not in depressive symptoms. Five studies found no significant association between legal status and symptoms of depression, anxiety, or PTSD [ 21 , 26 , 29 , 31 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our collaborating project in Sweden, with very similar study population, methodology and prevalence estimates of mental ill health [59,60], however, also found that close to 30% of participating refugees experienced pain/ discomfort at moderate/severe/extreme levels. Though, in the Swedish survey, pain was also measured by a single item from the standardized EQ-5D questionnaire developed by the EuroQol Group [69].…”
Section: The Burden Of Chronic Painmentioning
confidence: 62%
“…al. Our collaborating project in Sweden, with very similar study population, methodology and prevalence estimates of mental ill health [ 59 , 60 ], however, also found that close to 30% of participating refugees experienced pain/discomfort at moderate/severe/extreme levels. Though, in the Swedish survey, pain was also measured by a single item from the standardized EQ-5D questionnaire developed by the EuroQol Group [ 69 ].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, there was no difference in the proportion with anxiety and depression scores above cut-off when participants who returned the questionnaire within a month after study launch ( n = 433) were compared with those who responded later and after a reminder had been sent out ( n = 464). There was a tendency, however, that a higher proportion of early-responders had a PTSD score above cut-off [ 60 ]. This provides some evidence that willingness to participate (operationalized through how soon participants returned the questionnaire) was not strongly related to mental ill health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation